Financial statements analysis of Dutch Lady company for the 5 years period from 2005 – 2009 / Noor Hafizah Idros - Idros, Noor Hafizah (Faculty of Business and Management, 2011)
This study was carried out to discover the Financial Statements Analysis of Dutch Lady Company for the 5 Years Period From 2005 – 2009. The study looked at what definitions of financial statement analysis and the theory that relate with research. The main objective of this study is to Prepare and interpret financial statements in comparative and common-size form and compute and interpret financial ratios that would be most useful to a common stock holder, short and long-term creditor. This study was carried out in order to improve the level of profitability and reduce the expenses. I also referred previous findings and theory from online resources that being used to give an idea for completing this report. Observation is use to measure the financial income statements from 2006 until 2009. After that, I prepare and compute the comparative financial statements, common size financial statements and ratio analysis for describe whether the company is it in trouble in profitability measures. Finally, this paper makes some recommendations in respect of further suggestion in improving profit and reduces or minimizes the expenses.